Pattern of relapse and dosimetric analysis of a single dose 19 Gy HDR-brachytherapy phase II trial. (May 2020) - Gomez-Iturriaga, Alfonso; Buchser, David; Mayrata, Esther; San Miguel, Iñigo; Gonzalez, Alba; Suarez, Fernan; Martinez-Indart, Lorea; Minguez, Pablo; Espinosa, Jose; Perez, Fernando; Cacicedo, Jon; Casquero, Francisco
Highlights: HDR single fraction 19 Gy brachytherapy provides insufficient rates of biochemical and local control, in patients with localized prostate cancer. The pattern of relapse is predominantly local. HDR single fraction 19 Gy should not be used to treat favorable localized prostate cancer. Abstract: Purpose: To report the pattern of relapse within the prostate with reference to the initial site of disease in patients treated with single fraction 19-Gy. Methods and materials: Forty-four patients were treated according to a prospective study of single-fraction HDR-brachytherapy. Treatment was delivered using 192Ir to a dose of 19 Gy prescribed to the prostate. Patients who experienced a biochemical failure underwent a re-staging multiparametric MRI (mpMRI) and MRI-TRUS fusion biopsy to rule-out local recurrence. In patients with visible Dominant intraprostatic lesions (DIL) on pretreatment mpMRI, the site of local relapse was compared with the initial site of disease. The dose received by the site of recurrence was investigated. Results: The median follow-up period was 48 months (range 29–63). The PSA nadir was reached at 24 months follow-up, with a median value of 1.07 ng/mL. To date, 14 patients (32%) have experienced biochemical failure (4 patients low-risk and 10 intermediate-risk; p  = 0.013). Re-staging mpMRI was performed in 11/14 patients. Eleven patients underwent MRI-TRUS fusion biopsy confirming local relapse in all patients. The analysis of DVH of all 44 patients revealed that patients with biochemical failure had received significantly lower doses in terms of V100, V125 and D90 ( p  = 0.032, p  = 0.018 and p  = 0.018 respectively). In patients with DILs on diagnostic mpMRI, the mean D90 and D98 on DIL were lower for patients with biochemical failure. Conclusions: This dosimetric analysis demonstrates a dose-response relationship in patients treated with single fraction 19 Gy. Patients with intermediate risk disease, with visible DIL on mpMRI and patients treated with cooler implants have higher incidence of biochemical and local failure.